Potencial da aplicação de revestimentos para conservação pós-colheita da uva ‘Sweet globe’ cultivada em condições tropicais - Félix, Débora Tamara (2019)
In lower-middle region of the São Francisco Valley the vine cultivation has achieved success in terms of production and quality of grapes. However, the conservation of some cultivars needs to be extended in order to allow commercial advantages. Coatings have been used in fruits and vegetables in order to preserve the quality and extend the shelf life. The objective of this work was to identify coatings that, applied in pre-harvesting, allow greater preservation and maintenance of post-harvest quality in 'Sweet Globe' table grapes cultivated in the lowermiddle of the São Francisco Valley. The work was carried out with the 'Sweet Globe' vine. Three experiments were conducted in which coatings based on sodium alginate, caroxymethylcellulose (CMC) and chitosan were applied. In the first experiment were tested: 0.5%, 1.0% and 1.2% sodium alginate; 0.2%, 0.4% and 0.6% carboxymethylcellulose (CMC); 0.5%, 1.0% and 1.2% chitosan; and control in storage at 24,2 ± 0,3°C and 89,7 ± 3,1% of relative humidity (RU). In the latter, 0, 2, 4, 5 and 6 day evaluations were performed. In the second, 0.5% sodium alginate; 0,2% CMC; chitosan at 1.0% and control, under storage at -0.7 ± 0,5 °C and 86,1 ± 2,2% RU for 30 days, with transfer to 23.9 ± 0,1 °C and 85,7 ± 2,1% RU, for evaluation at 31, 32 and 33 days. In the latter, 0.5% sodium alginate; 0.2% CMC and control were applied, with the bunches stored at -0.3 ° C ± 0,4 and 84,3 ± 4,3 %RU for 38 days and maintained for 4 days at 24.4 °C ± 0,2 and 83,2 ± 4,9 %RU. Evaluations occurred at 0, 10, 20, 30, 35, 38, 39, 40, 41 and 42 days. Were analyzed: mass loss, berry abscission, appearance (turgidity of the stalk, spots and shriveled berries), respiratory rate, color components (L, C, H), firmness of the berries, elasticity of the bark, diameter of the central axis of the stink, diameter of the lateral branches of the stalks, titratable acidity, soluble solids, activity of polyphenoloxidase and peroxidase, yellow flavonoids and total extractable polyphenols. The experimental design was in randomized blocks, in factorial (coating x storage time), with three repetitions. In the first experiment, 0.5% alginate, 0.2% CMC and 1.0% chitosan maintained the quality of the grape, highlighting the variables appearance, weight loss and firmness. Bunches coated with 0.4% CMC and 0.5% chitosan were differentiated by the smaller size. The bunches of treatments CMC 0.2% and 0.4% showed more turgid stalks. In the second, better effects were observed with 0.2% CMC, 0.5% chitosan, for coloration, firmness and respiration. The CMC treatment promoted lower berry abcission and absence of spots up to 25º day. The turgidity of the stalks was preserved for up to 15 days. In the third, no treatment presented berry abscission and the stalks remained turgid until the 30 days. The CMC resulted in smaller variations in the yellow flavonoid content. In general, the coatings preserved the quality of ‘Sweet Globe®’ grape, however there is a need for adjustments in order to potentiate the effects.